Performance of Integrated Emergency Surgical Officers at Mizan-Tepi University Teaching Hospital, Mizan-Aman, Ethiopia: A Retrospective Cohort Study - Harrison, Margo S. (Obstet Gynecol Int, 2021)
INTRODUCTION: Surgical physician extenders are used in Ethiopia and sub-Saharan Africa where there is a lack of surgical providers. METHODS: We tested characteristics associated with and outcomes of births attended by an integrated emergency surgical officers (IESOs) as compared to midwives and physician providers. RESULTS: Of 1,000 women in our convenience sample, data on birth attendant was missing on 5 women (0.5%). Of the remaining women, almost three-fourths (73.6%, n = 732) of women were attended by a midwife, almost a quarter were attended by an IESO (24.4%, n = 243), 10 women were attended by a physician with a General Practitioner level of training (1.0%), 5 women were delivered by an Ob/Gyn resident (0.5%), and 5 women were attended by an Ob/Gyn (0.5%). Women had a higher likelihood of being attended by an IESO than a midwife if they underwent forceps-assisted (RR 88.4, p < 0.05), vacuum-assisted (RR 45.2, p < 0.05), or cesarean birth (RR 161.8, p < 0.05) as compared to an unassisted vaginal birth. IESOs are performing more operative vaginal and cesarean births than other delivery providers. Outcomes of their deliveries are worse than those of midwives, but this is likely due to the acuity level of the patients and not the provider type.